101k views
2 votes
Consider the equation StartFraction 5 Over 3 EndFraction v plus 4 plus StartFraction 1 Over 3 EndFraction v equals 8. v + 4 + StartFraction 5 Over 3 EndFraction v plus 4 equals 8 minus StartFraction 1 Over 3 EndFraction v. v = 8. What is the resulting equation after the first step in the solution? v +4 = 8 – v StartFraction 4 Over 3 EndFraction v plus 4 equals 8.v +4 = 8 4 + v = 8 – 4 plus v equals 8 minus StartFraction 5 Over 3 EndFraction v.v 2v + 4 = 8

2 Answers

5 votes

Answer: Option D

(D) 2v + 4 = 8

Explanation:

User Phae Deepsky
by
5.4k points
7 votes

Answer:

Option d.

Explanation:

The given equation is


(5)/(3)v+4+(1)/(3)v=8

We need to find the resulting equation after the first step in the solution.

First step: Combined like terms.


((5)/(3)v+(1)/(3)v)+4=8


((5)/(3)+(1)/(3))v+4=8


((5+1)/(3))v+4=8

On simplification we get


((6)/(3))v+4=8


2v+4=8

The resulting equation after the first step in the solution is 2v+4=8.

Therefore, the correct option is d.

User TimJ
by
5.9k points